Development of flank lesions in growing pigs after weaning: A case study - Norring, Marianna; Ko, Heng-Lun; Valros, Anna (Frontiers in Veterinary Science, 2023)
Flank lesions in pigs are a common yet poorly understood consequence of damaging social behavior. One group of pigs on a commercial farm with group lactation and late weaning, and with the history of flank lesions was studied. Skin lesions on the flanks, including linear and circular lesions, and tail lesions on 69 pigs were recorded six times during 5 weeks after weaning at the age of 9 weeks. Nosing behavior was scanned during six sessions with multiple scans. The associations of age, trunk whiteness, weight gain, sow parity, litter size, sex, and tail lesions with the number of circular and linear lesions were analyzed using linear mixed models. The number of linear lesions increased as pigs aged, and pigs with a higher weight gain had more linear lesions. Moreover, pigs with a whiter trunk color were scored with more lesions of both types. According to descriptive behavior data, nosing and biting behaviors were most frequent during weeks 2–4 after weaning at the age of 11–13 weeks. On average, seven circular flank lesions were found per pig during the experiment, at the age of 10 to 14 weeks. After the peak on day 17, their occurrence decreased. Skin lesion occurrence was related to a lighter skin color on the trunks of pigs. We recommend reporting skin color in connection with lesion scoring results. Nosing behavior and flank lesions both peaked from 2 to 4 weeks after weaning, suggesting that nosing behavior contributed to lesion development during this time.